Fuzzy Logic Mamdani-Based Simulation of Solanum Lycopersicum Fruit Sorter to Produce High-Quality Fruit Products - Siregar, Rahmat Fauzi; Affandi; Nasution, Arya Rudi; Hasanul Arifin; Harahap, Muhammad Alwi Ripay (Universitas Medan Area, 2024)
This research presents a novel approach utilizing Fuzzy Logic Mamdani-based simulation implemented through MATLAB and SolidWorks for sorting Solanum Lycopersicum fruits to achieve premium fruit quality. By integrating advanced computational tools, the simulation emulates intricate sorting processes, enabling precise decision-making akin to human judgment. This innovative methodology offers a promising avenue for improving fruit sorting efficiency and product quality in agricultural industries. This simulation system uses loadcell sensors, color sensors and PIR sensors as input. These inputs are used to control three servos and one DC motor. The fuzification process is carried out on both the input and output sides. Based on the results of the fuzification process, eighty-one rules were obtained and a fuzzy inference process was carried out using the intersection method. After carrying out the fuzzy inference process, it is continued with the defuzzification process. The result of the defuzzification value on the quality output is 7324.99 in the high set and the result of the simulation of the quality output value is 7250 in the high set. Thus, the accuracy level of the simulation's results is 98.98%. The simulation results show that the system is able to sort low, medium and high quality Solanum lycopersicum fruit.